Implementation Of Quality Of Work-Life System At Bank Syariah Indonesia In Parepare City - Angraeny; Akhsan; Yusran Bachtiar (Journal AK-99, 2023)
This study aims to find out how the implementation of the Quality of Work Life System at PT. Bank Syariah Indonesia in ParepareCity. The research conducted focuses on the implementation of quality of work-life system at PT Bank BNI Syariah Parepare City, where the bank here responds to employee needs by developing mechanisms to allow employees to give full contributions or participate in making decisions and managing their work life in the bank. The data analysis technique used is to reduce data, and present data to conclude. The results showed that the creation of quality of work life at Bank Syariah Indonesia Branch ofParepare included employee participation, compensation, job security, management ability to resolve conflicts, career development opportunities, employee pride in work, and adequate work environment facilities. When the quality of the work-life flow chart can be realized, it will have an impact on employee performance so that it can improve the quality of work.